DOI: 10.33915/etd.4297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diesel exhaust particles on allergic reactions and airway responsiveness in ovalbumin-sensitized brown Norway rats

Abstract: Diesel exhaust particles (DEP) are the major constituent of ambient particulate matter in urban environments and occupational settings. Exposure to DEP in combination with an allergen has been demonstrated to enhance allergen-related airway inflammation, immunoglobulin (Ig) E production, and airway responsiveness (AR) in human and in animal models. However, the mechanisms behind these effects of DEP are not yet fully understood. In this study, we compared the effects of short-term DEP exposure on ovalbumin (OV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 177 publications
(246 reference statements)
1
14
0
1
Order By: Relevance
“…In our current study, we determined that NO and ROS production continue after cessation of silica exposure and thus may, in part, be responsible for disease progression. Furthermore, particulate silica was determined to be highly associated with iNOS in AMs, unlike other particles, such as carbon black (Millecchia, unpublished data) and diesel exhaust particles (Dong et al, 2005), which are not associated with increased iNOS in AMs. Whether the iNOS upregulation is a direct result of silica phagocytosis, or whether other signals are triggering iNOS increases remains to be determined.…”
Section: Exposure (Days)mentioning
confidence: 96%
“…In our current study, we determined that NO and ROS production continue after cessation of silica exposure and thus may, in part, be responsible for disease progression. Furthermore, particulate silica was determined to be highly associated with iNOS in AMs, unlike other particles, such as carbon black (Millecchia, unpublished data) and diesel exhaust particles (Dong et al, 2005), which are not associated with increased iNOS in AMs. Whether the iNOS upregulation is a direct result of silica phagocytosis, or whether other signals are triggering iNOS increases remains to be determined.…”
Section: Exposure (Days)mentioning
confidence: 96%
“…Several studies have shown that persistent exposure to particulate air pollution poses a significant factor responsible for the observed increased prevalence of atopy [6e8,41e44]. Experimental studies examining the challenge with diesel exhaust particles in combination with allergens have shown a significantly higher allergen specific IgE induction compared to the challenge with the allergen alone [44]. Dong et al [44] demonstrated that exposure to diesel exhaust particles prior to ovalbumin sensitization in rats exacerbates the allergic responses to the subsequent challenge with OVA in OVA-sensitized rats.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies examining the challenge with diesel exhaust particles in combination with allergens have shown a significantly higher allergen specific IgE induction compared to the challenge with the allergen alone [44]. Dong et al [44] demonstrated that exposure to diesel exhaust particles prior to ovalbumin sensitization in rats exacerbates the allergic responses to the subsequent challenge with OVA in OVA-sensitized rats. Moreover, studies in people living in areas with high traffic have shown increased sensitization to outdoor allergens [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Diesel exhaust particles (DEP), which result from the incomplete combustion of diesel fuel, are a major component of airborne PM and have been largely studied for their role in enhancing immune responses in allergic diseases such as asthma. While multiple studies have documented the ability of inhaled DEP to impact and activate cells of the immune system [8][9][10], less is known about the effect of DEP on airway epithelial cells.…”
Section: Introductionmentioning
confidence: 99%